Surface modification of polyacrylonitrile based ultrafiltration membrane - Lohokare, Harshada R.; Kumbharkar, S. C.; Bhole, Yogesh S.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2006)
Ultrafiltration membrane based on polyacrylonitrile prepared by phase inversion method using zinc chloride as an additive showed more than 90% rejection for BSA and 90-110 Im(-2) h(-1) water flux. The surface modification of this membrane was studied using ethanolamine, triethylamine, sodium hydroxide, and potassium hydroxide solutions. The effect of base treatment time and temperature on water flux and rejection was investigated. The membranes exhibited swelling by NaOH treatment followed by deswelling by HCl post-treatment, similar to pH responsive membranes. The treatment by organic as well as inorganic bases improved water flux with a slight lowering in BSA rejection by dead-end mode type treatment. A 230% increase in water flux was achieved by sodium hydroxide treatment in crossflow mode without a noticeable pore swelling by SEM. The contact angle of the modified membranes was decreased as compared to the unmodified one indicating appreciable surface modification. As the treatment time or temperature increased, the ESCA analysis showed increased population of Na-carboxylate groups. (c) 2006 Wiley Periodicals, Inc.
Keywords: BSA rejection; chemical treatment; polyacrylonitrile membrane; surface modification; Ultrafiltration